A study on high temperature dry sliding wear of AA7050-T4 and effects of the test temperature on microstructure, corrosion behavior, hardness and electrical conductivity - Erol, Mahmut; Kisasoz, Alptekin; Yaman, Pasa; Karabeyoglu, Sencer Sureyya; Barut, Ugur (ELSEVIER, 2022)
In the present work, dry sliding wear of the AA7050-T4 at elevated temperatures was studied. Also, corrosion behavior, electrical conductivity, and hardness of the worn samples were investigated. The wear tests were carried out from room temperature to 250 degrees C for naturally aged AA7050 alloy. Worn samples were characterized by differential scanning calorimetry, X-ray diffraction, optical microscope, scanning electron microscope, and 3D profilometer analysis. Moreover, corrosion resistance, electrical conductivity, and hardness were examined to reveal the effect of elevated wear temperature on the properties of the samples. Structural examinations revealed that increasing wear test temperature induces phase transformation, and MgZn2 precipitates are occurred for the samples worn at 200 degrees C and 250 degrees C. Furthermore, it was seen that electrical conductivity is improved via the formation of MgZn2 precipitates. The sample worn at room temperature showed superior corrosion resistance compared to others.
Keywords: AA7050; Natural aging; Dry sliding wear; Electrochemical corrosion; ZN-MG ALLOYS; PRECIPITATION BEHAVIOR; ALUMINUM-ALLOY; CU ALLOY; AL; DIFFRACTION; STRENGTH; QUENCH; RETROGRESSION; EVOLUTION; Materials Science